Zein as a versatile biopolymer: different shapes for different biomedical applications. Issue 62 (6th December 2021) - Tortorella, Silvia; Maturi, Mirko; Vetri Buratti, Veronica; Vozzolo, Giulia; Locatelli, Erica; Sambri, Letizia; Comes Franchini, Mauro
Abstract : Zein a versatile biomaterial in the biomedical field. Easy to chemically functionalize with good emulsification properties, can be employed in drug delivery, fabrication of bioactive membranes and 3D scaffolds for tissue regeneration. Abstract : In recent years, the interest regarding the use of proteins as renewable resources has deeply intensified. The strongest impact of these biomaterials is clear in the field of smart medicines and biomedical engineering. Zein, a vegetal protein extracted from corn, is a suitable biomaterial for all the above-mentioned purposes due to its biodegradability and biocompatibility. The controlled drug delivery of small molecules, fabrication of bioactive membranes, and 3D assembly of scaffold for tissue regeneration are just some of the topics now being extensively investigated and reported in the literature. Herein, we review the recent literature on zein as a biopolymer and its applications in the biomedical world, focusing on the different shapes and sizes through which it can be manipulated.